Optimalisasi Platform Digital untuk Penguatan Branding Restoran Aroma Palopo - Pratiwi, Dwi Apriani; Jamil, Muhammad; Aris, Valentino (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the implementation and evaluate the optimization of digital marketing in strengthening the branding of Aroma Palopo restaurant through digital platforms. The research method used is associative quantitative approach with data collection through questionnaires to 25 respondents who are active followers of the instagram account @aromapalopohjfatmawati, as well as documentation of the digital activities of the restaurant. Data analysis was conducted using brand awareness, brand recall, brand recognition, and unaware of brand indicators measured through a Likert scale of 1-5. The results showed that the digital marketing strategy of Aroma Palopo restaurant through instagram has been able to increase brand awareness in the category enough with an average score of 3.11. The brand recognition dimension received the highest score of 3.32, which indicates that the audience is able to recognize the logo and design of restaurant content on social media. Meanwhile, brand recall reached a value of 3.24, indicating that some respondents could remember the brand without seeing the logo or content directly, while the top of mind dimension was still low with a value of 3.04, indicating that the brand has not become the main choice of consumers. Video content (Reels) is considered the most effective in increasing interaction, therefore, upload consistency, visual storytelling, active interaction, and the use of paid advertising are recommended to strengthen branding on social media.